Effect of the welding parameters on residual stresses in pipe weld using numerical simulation - Alhafadhi, Mahmood; Krállics, György (Design of Machines and Structures, 2020)
The objective of this article is to predict the residual welding stress in a dissimilar pipe weld. The 2D model, instead of 3D was used to reduce the time and cost of the numerical calculation. The 2D numerical simulation MSC MARC code is used to predict the residual stress developed during pipe welding. The present model was validated using hardness measurement. Good agreement was found between the measurement and numerical simulation results. The effects of welding parameters on residual stress field on the outer and inner surface were assessed. The effect of welding parameter (welding current) is examined. The axial and hoop residual stresses in dissimilar pipe joints of different thickness for pipe weld were simulated in outer and inner surfaces. When the other parameters remain fixed, and the current has great effect on the weld shape and size, and then affects the residual stress level significantly.